1970
DOI: 10.1002/jmor.1051310407
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic changes in the testis of the brook stickleback Eucalia inconstans (Kirtland)

Abstract: The cyclic changes in the testis of the five-spined stickleback Eucalia inconstans (Kirtland) were studied histologically. Specimens were trapped between July 1965 and July 1967 in a shallow pond near London, Ontario.A three-dimensional microscopic study showed a main vas deferens and a system of primary, secondary and tertiary tubules.The testis cycle was divided into seven arbitrary stages. Spawning takes placc from mid-April to mid-July. This is followed by the division of primary spermatogonia which are lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1975
1975
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…Histology indicated that a large number of tubules contained cysts with spermatocytes in the hybrid males, but only a small number of such tubules located near the outside of testis in the controls. In a closely related gasterosteid fish, brook stickleback ( Culaea inconstans ), spermatocyte formation completed in the first autumn of life, and most of the cysts filled with spermatocytes broke down prior to the winter season for spermiogenesis (Ruby and McMillan, 1970). Taking into account the similarity in the life cycles between the brook and ninespine sticklebacks (Ruby and McMillan, 1970;Goto et al ., 1979), the present result for hybrid males suggested delay or arrest of spermatogenesis reducing the number of spermatids and distorting their shape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histology indicated that a large number of tubules contained cysts with spermatocytes in the hybrid males, but only a small number of such tubules located near the outside of testis in the controls. In a closely related gasterosteid fish, brook stickleback ( Culaea inconstans ), spermatocyte formation completed in the first autumn of life, and most of the cysts filled with spermatocytes broke down prior to the winter season for spermiogenesis (Ruby and McMillan, 1970). Taking into account the similarity in the life cycles between the brook and ninespine sticklebacks (Ruby and McMillan, 1970;Goto et al ., 1979), the present result for hybrid males suggested delay or arrest of spermatogenesis reducing the number of spermatids and distorting their shape.…”
Section: Discussionmentioning
confidence: 99%
“…After embedding in paraffin, the entire gonad was sectioned transversally at 8 碌 m thickness and stained with Delafield's hematoxylin and eosin according to the standard procedures. Histological nomenclatures followed Ruby and McMillan (1970).…”
Section: Gonad Histologymentioning
confidence: 99%
“…Testicular maturation was assessed using the classification system based on the presence and relative proportions of the various spermatogenic cells. Such schemes have been adopted by Gokhale (1957), Hyder (1969, Hiroi & Yamamoto (1970), Ruby & McMillan (1970 and . Figure 2 shows monthly variations in gonadosomatic indices.…”
Section: Methodsmentioning
confidence: 99%
“…In Engraulis malabaricus, Punctus co/us (Desphandi & Nadkarni 1973), Euca/ia inconstans (Ruby & McMillan 1970) and salmonids (Henderson 1967), the main sperm ducts are short and extend superficially from the posterior parts of the testes, unlike those found in L dumerili and probably other Mugilidae. Apart from this and other minor differences, the position and macro-appearance of the testes of L. dumerili are very similar to those of other teleosts.…”
Section: Macro-morphology Of the Testesmentioning
confidence: 99%
“…Each testis is suspended by the mesorchium, which is continuous with the visceral peritoneum of the swim-bladder and which runs along the entire length of the testes, as in Eucalia inconstans (Ruby & McMillan 1970). The left testis is always the longer of the two and extends anteriorly to the middle cardiac part of the stomach, to which it is attached by connective tissue.…”
Section: Macro-morphology Of the Testesmentioning
confidence: 99%